Uji Aktivitas Antioksidan Pada Ekstrak Buah Kawista (Limonia Acidissima) Menggunakan Spektrofotometer UV-Vis - Rustiah, Waode; Umriani, Nur (Indonesian Journal of Chemical Research, 2018)
Antioxidant activity test has been done on kawista fruit. This study aims to determine the antioxidant activity of kawista based on the test using UV-Vis spectrophotometer conducted wavelength (l) 516 nm. The kawista fruit is extracted by reflux using methanol solvent. The extracts were made at concentrations of 50 ppm, 100 ppm, 150 ppm, 200 ppm and 250 ppm. The results showed that the antioxidant activity based on IC50 values obtained on kawista fruit extract samples had a concentration of 1275 mg / ml. The results obtained are at the level of IC50> 150 mg/ml, this indicates that the kawista fruit have weak antioxidant ability.